2021
DOI: 10.3390/cancers13122956
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial O-GlcNAc Transferase Interacts with and Modifies Many Proteins and Its Up-Regulation Affects Mitochondrial Function and Cellular Energy Homeostasis

Abstract: O-GlcNAcylation is a cell glucose sensor. The addition of O-GlcNAc moieties to target protein is catalyzed by the O-Linked N-acetylglucosamine transferase (OGT). OGT is encoded by a single gene that yields differentially spliced OGT isoforms. One of them is targeted to mitochondria (mOGT). Although the impact of O-GlcNAcylation on cancer cells biology is well documented, mOGT’s role remains poorly investigated. We performed studies using breast cancer cells with up-regulated mOGT or its catalytic inactive muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…Substrates are specific to the isoforms of OGT, and the three isoforms are expressed differently [20,21]. For instance, mOGT is expressed transiently and in much lower than ncOGT, due to its susceptibility to the cellular glucose level [22,23]. The exact mechanisms for substrate recognition by OGT are yet to be clarified; however, the adaptor protein hypothesis and non-specific O-GlcNAcylation are recognized as the plausible mechanisms [24][25][26][27].…”
Section: Substrate Recognition By Ogt and Ogamentioning
confidence: 99%
“…Substrates are specific to the isoforms of OGT, and the three isoforms are expressed differently [20,21]. For instance, mOGT is expressed transiently and in much lower than ncOGT, due to its susceptibility to the cellular glucose level [22,23]. The exact mechanisms for substrate recognition by OGT are yet to be clarified; however, the adaptor protein hypothesis and non-specific O-GlcNAcylation are recognized as the plausible mechanisms [24][25][26][27].…”
Section: Substrate Recognition By Ogt and Ogamentioning
confidence: 99%
“…Increases in O-GlcNAcylation of mitochondrial proteins have been observed upon high-glucose conditions [ 8 , 9 ], and recent work pointed to perturbation in the localization of mOGT in cardiomyocytes mitochondria from diabetic mice [ 10 ]. Several lines of evidence indicate that alteration of O-GlcNAc cycle disrupts mitochondrial homoeostasis [ 7 , 11 , 12 , 13 , 14 , 15 , 16 ], including alteration in reactive oxygen species production [ 14 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biochemistry and proteomic studies have revealed that hundreds of mitochondrial proteins are O-GlcNAcylated, including key proteins involved in mitochondria bioenergetics, such as components of the respiratory chain complexes, ATP synthase, pyruvate dehydrogenase, Krebs cycle, and lipid metabolism enzymes [ 8 , 13 , 16 , 20 , 21 , 22 , 23 , 24 ]. Although it cannot be excluded that some of these proteins are O-GlcNAcylated in the cytosol prior to their export into mitochondria, several proteins encoded by mitochondrial DNA, such as MTCO1 (cytochrome oxidase 1), COX2 (cytochrome oxidase 2), and MT-ND4 (NADH:ubiquinone oxidoreductase core subunit 4), were also shown to be O-GlcNAcylated, confirming that O-GlcNAc cycling must occur within mitochondria [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the biological role of O-GlcNAcylation remains less understood compared to other cell signalling PTMs such as phosphorylation, thousands of O-GlcNAc substrates have been identified or predicted [6][7][8][9][10][11]. O-GlcNAcylation is a ubiquitous PTM implicated in various aspects of cellular functions, including gene transcription, cell signalling, and stress response [2,4,12].…”
Section: Introductionmentioning
confidence: 99%
“…For this ubiquitous PTM, an unbiased proteomics-level investigation would be ideal for uncovering novel functions of interest. Advances in mass spectrometry have indeed allowed the proteomic profiling of many O-GlcNAc substrates in a range of studies and models [6][7][8][9][10][11]. Bioscience and added to the culture media at the appropriate concentration, with BSA serving as the vehicle control.…”
Section: Introductionmentioning
confidence: 99%